Relação entre força máxima de mordida e ângulo goníaco na mordida cruzada - Said, Angelica Da Veiga [UNIFESP] (2017)
Objective: To analyze the maximum bite force in unilateral posterior cross-bite and the correlation between maximum bite force and gonial angle in adults. Method: A total of 160 individuals, 88 males and 72 females, aged between 18 and 39 years old, were divided into two groups: without cross-bite, composed of 130 individuals (75 males and 55 females) and with cross-bite, consisting of 30 individuals (13 males and 17 females). The method consisted of the steps of anamnesis, evaluation of the occlusion, recording of the maximum bite force and registration of the gonial angle. The occlusion evaluation was performed to classify the occlusion in without or with cross-bite. The maximum bite force was recorded with a DDK / M model digital dynamometer (Kratos, São Paulo, Brazil) and in all subjects, three measurements were performed with the device positioned on the occlusal surface of the first molars, alternately, and with one minute interval between each series, and the averages are then calculated. The registration of the gonial angle was obtained with a goniometer measuring the right and left sides. The data collected were statistically analyzed by ANOVA, paired T-Student and Pearson's correlation, considering a significance level of 0.05 (5%). Results: There was greater maximum bite force in males, independently of the group and side; in the without cross-bite group there was difference of the maximum bite force between sides only in females; between groups, there was greater maximum bite force in males in the without cross-bite group. The correlations found between maximum bite force and gonial angle in both groups were negative or inversely proportional. Conclusions: The cross-bite group had a lower maximum bite force in males and the correlation between maximum bite force and gonial angle was negative, indicating that greater the maximum bite force, lower the gonial angle or vice versa. The direct measurement was shown as a good clinical option for recording the gonial angle.